Intertidal fishes : life in two worlds - Horn, Michael H.; Martin, Karen L. M.; Chotkowski, Michael Anthony (Academic Press, 1999)
Intertidal Fishes describes the fishes inhabiting the narrow strip of habitat between the high and low tide marks along the rocky coastlines of the world. It analyzes the specialized traits of these fishes that have adapted to living in the dynamic and challenging space where they are alternately exposed to the air and submerged in water with the ebb and flow of the tides. This book provides a comprehensive account of fishes largely overlooked in many previous studies of intertidal organisms and emphasizes how they differ from fishes living in other deeper-water habitats. Coverage includes air breathing, movements and homing, sensory systems, spawning and parental care, feeding habits, community structure, systematic relationships, distribution patterns, and the fossil record in the intertidal zone. Key Features * Written by an international team of 21 experts on intertidal fish biology * Worldwide coverage of intertidal fishes * Comprehensive phylogenetic listing of all fish families with intertidal members * Global biogeographic analysis involving over 700 species from 86 sites * Outlines field and laboratory methods pertinent to studying intertidal fishes * Thorough ecological coverage with chapters on vertical distribution, movements and homing, reproduction, feeding, and community structure * Covers the physiology of aerial and aquatic respiration, osmoregulation, and sensory systems.